Management of Sports Injuries and Physical Rehabilitation of Badminton Athletes: A Qualitative Analysis of Kevin Sanjaya Sukamuljo and Marcus Fernaldi Gideon - Akhmad Kelvin Ferdiantono; Aprilyan Putra Bimantoro (Universitas Negeri Surabaya, 2025)
Background: Badminton’s high-intensity demands (strength, speed, agility, endurance) elevate musculoskeletal injury risk in elite athletes. Objectives: To analyze injury management and physical rehabilitation experienced by Kevin Sanjaya Sukamuljo and Marcus Fernaldi Gideon using a qualitative, secondary-data design. Methods: Qualitative content analysis synthesizing interviews, news reports, and match summaries about injury history, management, and rehabilitation; themes were derived by open–axial–selective coding. Results: Three themes emerged: (1) Injury typology and load (hamstring, knee, ankle, back, chronic shoulder); (2) Management pathways integrating physical therapy and sport therapy; (3) Rehabilitation and return-to-play (RTP) decision-making emphasizing progressive loading, monitoring, and strategic withdrawal. Illustrative quotations accompany each theme. Conclusion: Integrated physical therapy, sport therapy, and systematic rehabilitation—personalized to injury type—are essential to restore performance and prevent reinjury in elite badminton. Keywords: badminton; physical therapy; sport therapy; rehabilitation; injury management; qualitative analysis